Analysis of NF-κB Pathway Proteins in Pediatric Hodgkin Lymphoma: Correlations with EBV Status and Clinical Outcome—A Children's Oncology Group Study. (30th December 2012) - Horton, Terzah M.; Sheehan, Andrea M.; López-Terrada, Dolores; Hutchison, Robert E.; Narendra, Sonia; Wu, Meng-Fen; Liu, Hao
Abstract : Constitutively active nuclear factor-κ B (NF-κ B) is integral to the survival of Hodgkin/Reed-Sternberg cells (H/RS) in Hodgkin lymphoma (HL). To investigate NF-κ B pathway proteins in pediatric HL, we utilized a tissue microarray compiled from 102 children enrolled in the Children's Oncology Group intermediate-risk clinical trial AHOD0031 (56 male, 78 Caucasian, median age 15 years (range 1–20 years), 85 nodular sclerosing subtype, 23 Epstein-Barr virus (EBV) positive, and 24 refractory/relapsed disease). We examined the intensity, localization, and pathway correlations of NF-κ B pathway proteins (Rel-A/p65, Rel-B, c-Rel, NF-κ B1, NF-κ B2, Iκ B-α, IKK-α, IKK-β, IKK-γ /NEMO, NIK, and A20), as well as their associations with EBV status and clinical outcome. NF-κ B pathway proteins were overexpressed in pediatric HL patients compared to controls. Patients with EBV− tumors, or with rapid early therapy response, had tightly coordinated regulation of NF-κ B pathway proteins, whereas patients with EBV+ tumors, or slow early therapy response, had little coordinated NF-κ B pathway regulation. High NIK expression was associated with a slow response to therapy and decreased EFS. Elevated Rel-B, NIK, and the NF-κ B inhibitor A20 were associated with decreased EFS in multivariate analysis. These studies suggest a pivotal role for the NF-κ B pathway in therapy response and patient survival in Hodgkin lymphoma.